Ankylosed joint replacement with custom total joint prosthesis and custom miniplates. (Research, Society and Development, 2020)
When managing a severely ankylosed joint in a patient with a history of multiple previous operations since the development phase, it is necessary besides the total joint replacement also the orthognathic surgery. Miniplates and total joint custom-made prosthesis are the state of arts in accuracy and precision; therefore use them concurrently in a complex surgery, such this, is a suitable treatment option. A 44-year-old male patient with bilateral  temporomandibular joint ankylosis where the TMJ architecture was completely replaced by a large bone mass was treated through orthognathic surgery with customized cutting guides and customized material for maxilla, jaw and chin fixation, in addition to the installation of two complete custom-made joint-prosthesis in one-stage surgery. This is the first report in the literature using custom Miniplates and Joint-Prosthesis for treatment of Ankylosis. The treatment was successful and the patient benefited from adequate aesthetics and function.